COVID-19-related myocarditis and cholinergic anti-inflammatory pathways (2020)
Coronavirus disease (COVID-19), caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), is currently in a pandemic outbreak and has become a global health issue. In addition to primarily involving the respiratory system, myocarditis is considered an important and fatal lesion in patients with COVID-19. However, effective therapeutic methods are currently lacking. The cholinergic anti-inflammatory pathway (CAP) has been demonstrated to suppress pro-inflammatory cytokine production and control inflammation in sepsis and other medical conditions. Therefore, the CAP may be a potential and effective therapeutic method for COVID-19-related myocarditis. This article reviews the relationship between COVID-19-related myocarditis and the CAP and discusses the CAP as a potential therapeutic modality in the treatment of COVID-19-related myocarditis.